Universal Precautions in Cesarean Delivery in Patients with HIV - Irma Kania Safitri; Astrid Pratidina Susilo; Setyawan Nurtanio (Jurnal Kedokteran Mulawarman, 2022)
HIV infection (Human Immunodeficiency Virus) is a spectrum of diseases that attack immune cells, including primary infection, with or without the acute syndrome, asymptomatic stage, to advanced stage, with AIDS being the final stage of HIV infection. HIV transmission can occur from an HIV-positive mother to her baby in her womb, known as vertical transmission. This can occur through the placenta during pregnancy (intrauterine), during delivery (intrapartum), or postpartum through breast milk (ASI). Lack of knowledge of patients/families about HIV/AIDS, wrong beliefs about HIV/AIDS, and the way it is transmitted, can lead to various false stigmas in society and health workers and can cause feelings of being excluded/ostracized by certain families and groups. Handling and care for patients with HIV is the same as for patients with other infectious diseases, namely by applying the Universal Precaution principle with the standards set to prevent HIV transmission to medical officers on duty, so it is essential to understand and comply with health workers to apply universal precautions so as not to be infected.